A practical method for clinical veterinary use: Use of dentine hydroxyapatite (DHA) as a graft material - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2006)
This study demonstrates the use of human dentine derived hydroxyapatite (DHA) as an easily prepared graft material in 23 dogs and 5 cats with various orthopaedic problems. Results of these cases were evaluated clinically and radiographically. This study reveals that DHA can be used safely in animals and is an effective graft material.
Keywords: hydroxyapatite; fracture; bone; graft; osseointegration